Circulating Tumor DNA in Identifying Resistant Sub-Clones Post EGFR Blockade: Implications for EGFR Rechallenge - Chennamadhavuni, Adithya; Kasi, Pashtoon Murtaza (Frontiers in Oncology, 2022)
For patients with metastatic RAS/RAF wild-type refractory colorectal cancer, the question of anti-EGFR therapy rechallenge often comes up after initial use. However, not all patients derive benefit. It is now well known that these tumors acquire mechanisms of resistance in the mitogen-activated protein kinase (MAPK) pathway, which can be detected on circulating tumor DNA (ctDNA)-based testing. We present a series of patients who had serial testing post-EGFR blockade showing its feasibility and value. This would have implications for EGFR rechallenge. We reviewed records for patients who were initially noted to be RAS/RAF wild-type on tissue, who received prior anti-EGFR therapy and then subsequently had at least one circulating tumor DNA-based testing. These patients also had tissue-based genomic testing obtained earlier as part of their standard of care, alongside serial ctDNA-based testing that was done later when subsequent lines of therapy were being decided. The median duration of initial prior anti-EGFR therapy was around 10 months. Known acquired mechanisms of resistance were noted in 100% of the cases. These included KRAS, NRAS, extracellular domain mutations in EGFR, and BRAF mutations. Interestingly, the levels of the sub-clones expressed in variant allele fraction percentage varied and decreased over time in relation to timing of the prior EGFR exposure. Additionally, these were noted to be polyclonal, and the number of clones also varied including some disappearing over time during non-EGFR-based therapy (EGFR holiday). Patients’ post-EGFR blockade may have multiple mechanisms of acquired resistance that can be easily detected on non-invasive liquid biopsies. These patients do not benefit from EGFR rechallenge based on the results of the recently reported CRICKET (NCT02296203) and CAVE (NCT04561336) clinical trials. Furthermore, excluding these patients from EGFR rechallenge is already being adopted in prospectively done clinical trials, e.g., the CHRONOS study (NCT03227926). Rechecking the liquid biopsy plasma RAS/RAF status is one thing that may be incorporated into practice with EGFR rechallenge only a consideration if acquired mechanisms of resistance are absent.